A Case Report Describing the Use of Point of Care Ultrasound to Guide Successful Cardiopulmonary Resuscitation After Unanticipated Arrest in Ambulatory Surgery. Issue 10 (15th May 2019) - Hollon, McKenzie M.; Gershon, Raphael; D'Souza, Adam; Faloye, Abimbola
Abstract : We present a case of a 41-year-old man who suffered cardiac arrest after induction of general anesthesia for an ambulatory ophthalmologic procedure. In this report, we highlight the use of focused transthoracic echocardiography by the anesthesia team to guide a prolonged resuscitation. Emergency room and critical care physicians have described the use of focused echocardiography to aid in diagnosing correctible causes of cardiac arrest, predicting outcomes, and in decision making regarding termination of resuscitation. We discuss benefits and barriers to anesthesiologists incorporating focused cardiac ultrasound into the perioperative arena.